Hydrothermal synthesis and electrochemical properties of α-MoO 3 nanobelts used as cathode materials for Li-ion batteries - Phuruangrat A. (2014)
Uniform α-MoO 3 nanobelts were successfully synthesized by the hydrothermal process at 180°C for 20 h of the acidic solutions with different pH values of 0-0.75, adjusted using HCl (conc.). XRD and SEM results revealed that the pH of the precursor solutions played an important role in the phase, impurities, and morphology of the products. At the pH=0, the perfect α-MoO 3 nanobelts with a few tens of microns long were synthesized. By the TEM characterization, orthorhombic MoO 3 has a distinctive layered structure along the [010] direction, consisting of distorted MoO 6 octahedrons connected by common corners along the [100] direction and common edges along the [001] direction. The electrochemical measurement showed that the α-MoO 3 nanobelts have high specific charge capacity. © 2012 Springer-Verlag.